Tracking post-infectious fatigue in clinic using routine Lab tests. Issue 1 (December 2016) - Harvey, Jeanna; Broderick, Gordon; Bowie, Alanna; Barnes, Zachary; Katz, Ben; O'Gorman, Maurice; Vernon, Suzanne; Fletcher, Mary; Klimas, Nancy; Taylor, Renee
Abstract Background While biomarkers for chronic fatigue syndrome (CFS) are beginning to emerge they typically require a highly specialized clinical laboratory. We hypothesized that subsets of commonly measured laboratory markers used in combination could support the diagnosis of post-infectious CFS (PI-CFS) in adolescents following infectious mononucleosis (IM) and help determine who might develop persistence of symptoms. Methods Routine clinical laboratory markers were collected prospectively in 301 mono-spot positive adolescents, 4 % of whom developed CFS (n  = 13). At 6, 12, and 24 months post-diagnosis with IM, 59 standard tests were performed including metabolic profiling, liver enzyme panel, hormone profiles, complete blood count (CBC), differential white blood count (WBC), salivary cortisol, and urinalysis. Classification models separating PI-CFS from controls were constructed at each time point using stepwise subset selection. Results Lower ACTH levels at 6 months post-IM diagnosis were highly predictive of CFS (AUCp  = 0.02). ACTH levels in CFS overlapped with healthy controls at 12 months, but again showed a trend towards a deficiency at 24 months. Conversely, estradiol levels depart significantly from normal at 12 months only to recover at 24 months (AUCp  = 0.02). Finally, relative neutrophil count showed a significant departure from normal at 24 months in CFS (AUCp  = 0.01). Expression of these markers evolved differently over time between groups. Conclusions Preliminary results suggest that serial assessment of stress and sex hormones as well as the relative proportion of innate immune cells measured using standard clinical laboratory tests may support the diagnosis of PI-CFS in adolescents with IM.